ChemInform Abstract: Rhodium‐Catalyzed Ketone Methylation Using Methanol under Mild Conditions: Formation of α‐Branched Products. Issue 30 (29th July 2014) - Chan, Louis K. M.; Poole, Darren L.; Shen, Di; Healy, Mark P.; Donohoe, Timothy J.
Abstract Doubly alkylated ketones can be prepared from methyl ketones and two different alcohols by using a sequential one‐pot iridium‐ and rhodium‐catalyzed process [reaction of (VI)].